Performance analysis in football-specific tests by para-footballers with cerebral palsy: implications for evidence-based classification - Yanci, J.; Castillo, D.; Iturricastillo, A.; Aracama, A.; Roldan, A.; Reina, R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The objectives of this study were to analyze whether there were differences among para-footballers with different types and degrees of brain impairment (ie, bilateral spasticity, athetosis/ataxia, unilateral spasticity, minimum impairment criteria, or no impairment) in performing 3 football-specific tests requiring ball dribbling, to analyze whether there was an association among the results obtained in the 3 tests, and to determine whether the performance in the tests was associated with competitive level, level of training, or years` experience in para-footballers with cerebral palsy (CP).